2002
DOI: 10.1007/s00259-002-0878-2
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of 18F-FDG PET in the post-therapy surveillance of endometrial carcinoma

Abstract: Abstract. The aim of this study was to assess the usefulness of fluorine-18 fluoro-2-deoxy-D-glucose positron emission tomography (FDG PET) in the post-therapy surveillance of endometrial carcinomas. Forty-one fully corrected whole-body PET studies were performed in 34 women with previously treated endometrial cancers as a part of their follow-up programme. In 28 studies, FDG PET was indicated to localise a recurrence suspected at the control visits on the basis of clinical examination and/or radiological abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(65 citation statements)
references
References 38 publications
0
55
0
10
Order By: Relevance
“…Several reports indicated that 18 F-FDG PET is useful for managing pre-and postoperative patients with endometrial carcinoma mainly by detecting lymph node metastasis (14)(15)(16)(17). The classification of tumor characteristics determined by 18 F-FDG uptake and the 18 F-FDG-to-18 F-FES ratio could play an important role in the differential diagnosis of endometrial lesions and in deciding the therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicated that 18 F-FDG PET is useful for managing pre-and postoperative patients with endometrial carcinoma mainly by detecting lymph node metastasis (14)(15)(16)(17). The classification of tumor characteristics determined by 18 F-FDG uptake and the 18 F-FDG-to-18 F-FES ratio could play an important role in the differential diagnosis of endometrial lesions and in deciding the therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent years have seen the development of other radiopharmaceuticals suitable for detecting NETs [14][15][16], but under certain circumstances, F-18-FDG PET can also be of diagnostic importance in NET patients with high proliferation index [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…According to these studies the contribution of PET scan to treatment planning seems to be superior to CTscan due to its higher sensitivity for the detection of metastasis [32][33][34]36]. Yet, like CT-scans, the value of a PET scan is limited in the detection of pulmonary micro metastasis [35,37].…”
Section: Discussionmentioning
confidence: 99%
“…The role of FDG PET scan has been studied prospectively in patients with recurrent cervical cancer and did alter treatment in 55% -65% of these patients [32,33]. In two small series of patients with endometrial cancer FDG-PET scan was studied in follow-up and resulted in treatment adjustment in 33% -35% of the patients [34,35]. According to these studies the contribution of PET scan to treatment planning seems to be superior to CTscan due to its higher sensitivity for the detection of metastasis [32][33][34]36].…”
Section: Discussionmentioning
confidence: 99%